Strategi Komunikasi Pemasaran Berbasis Lingkungan dalam Meningkatkan Kunjungan Wisatawan di Pantai Camplong, Kabupaten Sampang - Hafidlatul Fauzuna; Fathul Qorib; Akhmad Haries Yulianto; Lutfiah Malika Putri (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The intense business competition is also evident in the tourism sector, including at Camplong Beach. To increase tourist visits, effective marketing communication strategies based on environmental sustainability are required. This study aims to analyze how environmentally-based marketing communication strategies are applied at Camplong Beach, focusing on raising awareness and interest among tourists in preserving the beach environment. This research uses a qualitative approach with field research methods involving interviews, observations, and documentation. This research refers to the IMC (Integrated Marketing Communication) theory which consists of advertising, personal selling, sales promotion, public relations and direct marketing. The findings indicate that Camplong Beach implements several marketing communication strategies, including: (a) Advertising through social media highlighting natural beauty and calls for environmental preservation, (b) Personal selling that educates tourists about beach cleanliness, (c) Sales promotions such as discounts for groups, (d) Public relations through beach clean-up activities and collaborations with related institutions, and (e) Direct marketing through personal experiences and proposal submissions to stakeholders. These strategies have proven to attract more tourists and support sustainable tourism concepts at Camplong Beach.